Islamic Ethics of Disagreement and the Use of Social Media in the Contemporary Era: A Research and Analytical Study in Light of Urdu Exegetical Literature - Mr Abdur Rafiq; Dr Ilyas Ahmad (Journal of Religion and Society, 2025)
This study examines the Islamic ethics of disagreement and their application to contemporary social media discourse, drawing on Urdu exegetical literature. Islamic teachings emphasize wisdom, respectful dialogue, sincerity, and truthfulness as essential principles governing differences of opinion. In contrast, current online behavior is often marked by emotional reactions, personal attacks, misinformation, and the pursuit of visibility, leading to polarization and social fragmentation.The analysis highlights the gap between Qur’anic guidelines for ethical disagreement and the prevalent patterns of digital communication. It shows that the erosion of decorum on social media undermines scholarly engagement, fuels sectarianism, and weakens communal cohesion. The study concludes that fostering responsible online conduct, promoting research-based dialogue, and integrating ethical training are necessary for ensuring that disagreement remains constructive and aligned with Islamic moral frameworks.